Abacaecus n. gen. walterrossii n. sp., a notable hypogean carabid species from Sierra Leone, Western Africa (Coleoptera, Carabidae, Pterostichinae) - Allegro, Gianni; Giachino, Pier Mauro (Zootaxa, 2020)
Abacaecus n. gen. walterrossii n. sp., a notable blind species from Sierra Leone, is described. A. walterrossii n. sp. probably belongs to a separated phyletic lineage inside Abacetini sensu lato and is the first recorded blind African species of this tribe. It is also compared to Pterostillichus caecus Straneo, another African blind species of uncertain affinities, of which is given an integrative description enriched by illustration of a few characters.